THE INFLUENCE OF EXPORT AND IMPORT TOWARD ECONOMIC GROWTH IN THE UNITED STATES OF AMERICA, PERIODE 2010-2019 - Andi Triyawan; Achmad Fajaruddin; Mawardhea Fithri Anugrah (Journal of Islamic Economics and Philanthropy, 2021)
Export and import are one of the long-running international trade activities and are still ongoing. The United States is one of the importing countries of Indonesia in the food and technology industry. In the analysis of this research, the aim is to determine how far the influence of US exports and imports on economic growth in Indonesia. In this study using quantitative methods using secondary data sourced from the world bank with panel data which is the time series for the 2010 - 2019 period. The results of this study indicate that there is no significant effect between export value and import value together on GDP value. . So from this case it can be concluded that the export value and the import value together have no effect on the GDP value in the United States of America. Meanwhile, it can be concluded that partially the import value has no effect on the value of GDP in the United States of America.Export and import are one of the long-running international trade activities and are still ongoing. The United States is one of the importing countries of Indonesia in the food and technology industry. In the analysis of this research, the aim is to determine how far the influence of US exports and imports on economic growth in Indonesia. In this study using quantitative methods using secondary data sourced from the world bank with panel data which is the time series for the 2010 - 2019 period. The results of this study indicate that there is no significant effect between export value and import value together on GDP value. . So from this case it can be concluded that the export value and the import value together have no effect on the GDP value in the United States of America. Meanwhile, it can be concluded that partially the import value has no effect on the value of GDP in the United States of America.